The effects of play therapy on anxiety among pediatric patients with cancer at the Philippines General Hospital - Berongoy, Gayle; Fuentes, Sheryl; Paguio, Jenniffer; Sanchez, Mary Ruth. (Manila College of Nursing University of the Philippines Manila, 2003)
A Health Service must always be available in every institution since this shall attend to the physical, mental, social and emotional health of the students. Such institution is UP Manila.

UP Manila has its own school Health Service at the PGH called UP-PGH Health Service where physical examination for students, as well as PGH employees, is being done annually. However, previous study revealed underutilization of the services of the Health Service. This drove the researchers to investigate on the scope and utilization of the services and the factors affecting its utilization.

This research opted to determine the relationship between awareness and utilization of Health Service and to describe perception of UP Manila undergraduate students of health-related courses toward the UP-PGH Health Service.

This study used Descriptive Correlational Design. This analyzed how variables are associated with each other whether positively or negatively. The sampling design, on the other hand, used is the Simple Random Sampling Method wherein 16 students for each undergraduate year level from all the health-related colleges namely CAMP, CM, CN, CP, CPH and CD, were randomly selected. A pretest was done on 12 selected nursing students, who were not included as members of sample population, 3 from each year level.

The variables that were taken into consideration were awareness and utilization. The variable awareness was subdivided into the following dimensions: location, operating schedule, services offered and requirements needed. Utilization, on the other hand, was confined to the dimension of availed services aside from the annual PE. All data gathered were treated nominally.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, February 2003.
Keywords: Intensive nursing experience -- Hospital-based.